2022
DOI: 10.3389/fpls.2022.959784
|View full text |Cite
|
Sign up to set email alerts
|

Rice Paddies Reduce Subsequent Yields of Wheat Due to Physical and Chemical Soil Constraints

Abstract: Yields of wheat crops that succeed rice paddy crops are generally low. To date, it has been unclear whether such low yields were due to rice paddies altering soil physical or mineral characteristics, or both. To investigate this quandary, we conducted field experiments in the Jianghan Plain to analyze differences in the spatial distribution of wheat roots between rice-wheat rotation (RW) and dryland-wheat rotations (DW) using a range of nitrogen treatments. Dryland wheat crops were preceded by either dryland s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Straw returning is an efficacious method which is being promoted for addressing the excessive straw generation and for mitigating the environmental pollution associated with straw burning. Previous studies have demonstrated that the practice of returning straw to the field significantly impacts on the physicochemical properties of the soil, as well as on the microbial community [3,15,41]. The findings of our study indicate that the varied rates of nitrogen application and rice straw return differentially impacted soil physicochemical properties and wheat growth at the different growth stages, and thus influenced wheat grain yield (Tables 1-3).…”
Section: Effect Of Rice Straw and N Fertilization On Soil Physicochem...mentioning
confidence: 48%
See 1 more Smart Citation
“…Straw returning is an efficacious method which is being promoted for addressing the excessive straw generation and for mitigating the environmental pollution associated with straw burning. Previous studies have demonstrated that the practice of returning straw to the field significantly impacts on the physicochemical properties of the soil, as well as on the microbial community [3,15,41]. The findings of our study indicate that the varied rates of nitrogen application and rice straw return differentially impacted soil physicochemical properties and wheat growth at the different growth stages, and thus influenced wheat grain yield (Tables 1-3).…”
Section: Effect Of Rice Straw and N Fertilization On Soil Physicochem...mentioning
confidence: 48%
“…The field is used for wheat and rice rotation. The Jianghan Plain is one of major grain production bases in Hubei Province, and forms a key part of the wheat-growing areas in the Yangtze River Basin [41]. The Experimental Farm Station is characterized by a typical subtropical monsoon climate in the middle-lower Yangtze River Basin of China.…”
Section: Experimental Site Description and Planting Materialsmentioning
confidence: 99%
“…The yield difference between different cropping systems is mainly caused by differences in the soil environment [23]. In the water and drought rotation system, the soil surface structure formed in the rice season and the compact plow layer formed over the years result in significant differences in soil structure between the wheat planted after rice and the wheat planted in dryland [24].…”
Section: Analysis Of Factors Influencing Yield Differences Among Plan...mentioning
confidence: 99%